ЗА ПРЕВОДОТ НА НЕКОИ СПЕЦИФИЧНИ КУЛТУРНИ ФЕНОМЕНИ ОД ГЕРМАНСКИ НА МАКЕДОНСКИ ЈАЗИК ВО ШНИЦЛЕРОВАТА НОВЕЛА „ПОРУЧНИКОТ ГУСТЛ“ (Philological Studies, 2019)
This article offers an analysis from a translational perspective of some specific cultural phenomena present in literature. The focus is placed on the novella Lieutenant Gustl by Arthur Schnitzler, translated into Macedonian by Marina Nishliska. The paper begins with the term specific cultural phenomenon, and then follows a critical review of methods used in the novel for overcoming problems when translating the specific cultural phenomenon. Lexemes of material culture, differences in the usage of capital letters and some communication phenomena (such as direct addressing, usage of vocative and vulgarisms as lexical variations from diastratic aspect) are taken in for analysis. Where translation does not meet the criteria of quality, better solutions are offered for translating such phenomena.
Keywords: specific cultural phenomenon, literary translation, literary translator, communication